The Relationship between Target Costing Method and Pricing -Development of Products in Industrial Companies - Al-Khasawneh, Shadi Maher; Jrairah, Talal Souliman; Endut, Wan Anisah; Nik Mohd Rashid, Nik Mohd Norfadzilah (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2019)
This study aimed at identifying the relationship between target costing method in product pricing, as well as identify the relationship of target costing in products development in industrial companies operating at Al-Hassan industrial zone located in Irbid. The population of this study was 51 companies which implement the target costing method. Out of those 51 companies, 35 companies were randomly chosen to participate in this study. The questionnaire has been prepared and distributed to financial managers, production managers, marketing managers, and accountants, where each company got 4 questionnaires. One sample T-test in SPSS was used to examine the hypotheses of this study. The results revealed that the application of target costing method leads to pricing products, as well as that the application of target costing system leads to the development of products in industrial companies operating at Al-Hassan industrial zone.